Microglia and Brain Plasticity in Acute Psychosis and Schizophrenia Illness Course: A Meta-Review - De Picker, Livia J.; Morrens, Manuel; Chance, Steven A.; Boche, Delphine (Frontiers in Psychiatry, 2017)
OBJECTIVE: Schizophrenia poses a tremendous health, social, and economic burden upon patients and society, indicating current treatment options remain inadequate. Recent findings from several lines of evidence have pointed to the importance of immune system involvement in not only premorbid neurodevelopmental, but also subsequent symptom generation and ageing processes of brain change in schizophrenia. In this meta-review, we use the summarized evidence from recent quantitative systematic reviews and meta-analyses of several subspecialties to critically evaluate the hypothesis that immune-related processes shape the symptomatic presentation and illness course of schizophrenia, both directly and indirectly through altered neuroplasticity. METHODS: We performed a data search in PubMed for English-language systematic reviews and meta-analyses from 2010 to 2017. The methodological quality of the systematic reviews was assessed with the AMSTAR instrument. In addition, we review in this paper 11 original publications on TSPO PET imaging in schizophrenia. RESULTS: We reviewed 26 systematic reviews and meta-analyses. Evidence from clinical observational studies of inflammatory or immunological markers and randomized controlled drug trials of immunomodulatory compounds as add-on in the treatment of schizophrenia suggests psychotic exacerbations are accompanied by immunological changes different from those seen in non-acute states, and that the symptoms of schizophrenia can be modified by compounds such as NSAID and minocycline. Information derived from post-mortem brain tissue analysis and PET neuroimaging studies to evaluate microglial activation have added new perspectives to the available evidence, yet these results are very heterogeneous. Each research domain comes with unique opportunities as well as inherent limitations. A better understanding of the (patho-)physiology of microglial cells and their role in neuroplasticity is key to interpreting the immune-related findings in the context of schizophrenia illness exacerbations and progression. CONCLUSIONS: Evidence from clinical studies analyzing patients’ blood and cerebrospinal fluid samples, neuroimaging and post-mortem brain tissue suggests that aberrant immune responses may define schizophrenia illness’ course through altered neuroplasticity representing abnormal ageing processes. Most findings are however prone to bias and confounding, and often nonspecific to schizophrenia, and a multidisciplinary translational approach is needed to consolidate these findings and link them to other schizophrenia hypotheses.